Approaches to social research : the case of deaf studies - Young, Alys; Temple, Bogusia (Perspectives on deafness., 2014)
In Approaches to Social Research: The Case of Deaf Studies, Alys Young and Bogusia Temple explore the relationship between key methodological debates in social research and the special context of studies concerning d/Deaf people(s). The book is organized around 7 topics: being d/Deaf as a site of contested identity and representation; epistemology and the boundaries of claims for population specific and plural epistemologies; ethics and the implications of collective identity on standard ethical principles and practices; populations and sampling given the highly heterogeneous nature of d/Deaf.